Case management of childhood pneumonia in developing countries. - Ayieko, P; English, M (2007)
BACKGROUND: Pneumonia is a leading cause of morbidity and mortality in children worldwide. Appropriate management depends on accurate assessment of disease severity, and for the majority of children in developing countries the assessment is based on clinical signs alone. This article reviews recent evidence on clinical assessment and severity classification of pneumonia and reported results on the effectiveness of currently recommended treatments. METHODS: Potential studies for inclusion were identified by Medline (1990-2006) search. The Oxford Center for Evidence Based Medicine criteria were used to describe the methodologic quality of selected studies. RESULTS: In the included studies the sensitivity of current definitions of tachypnea for diagnosing radiologic pneumonia ranged from 72% to 94% with specificities between 38% and 99%; chest indrawing had reported sensitivities of between 46% and 78%. Data provide some support for the value of current clinical criteria for classifying pneumonia severity, with those meeting severe or very severe criteria being at considerably increased risk of death, hypoxemia or bacteremia. Results of randomized controlled trials report clinically defined improvement at 48 hours in at least 80% of children treated using recommended antibiotics. However, a limitation of these data may include inappropriate definitions of treatment failure. CONCLUSION: Particularly with regard to severe pneumonia, issues that specifically need to be addressed are the adequacy of penicillin monotherapy, or oral amoxicillin or alternative antibiotics; the timing of introduction of high-dose trimethoprim-sulfamethoxazole in children at risk for or known to be infected by HIV and the value of pulse oximetry.